Home Sleep Testing for the Diagnosis of Obstructive Sleep Apnea—Indications and Limitations - Cruz, Sharon De; Littner, Michael R.; Zeidler, Michelle R. (Seminars in Respiratory and Critical Care Medicine, 2014)
The increasing prevalence and recognition of obstructive sleep apnea (OSA) coupled with an awareness of its detrimental health consequences has resulted in the need for timely and cost efficient access to diagnostic sleep testing and treatment. As a result, increased emphasis is being placed on simplified ambulatory models for the diagnosis and treatment of OSA using home sleep testing (HST). An ambulatory sleep program requires the combination of clinical assessment for identifying patients at high risk for OSA, HST for the diagnosis of OSA, and home auto-titrating positive airway pressure units for treatment. Randomized control trials evaluating the efficacy of this ambulatory approach to diagnose and treat OSA in high-risk patients without significant medical comorbidities reveal the potential for equivalent patient outcomes when compared with the use of polysomnography and in-laboratory continuous positive airway pressure titration.
Keywords: obstructive sleep apnea; home sleep test; auto-titrating positive airway pressure; respiratory disturbance index